2019
DOI: 10.1136/rmdopen-2019-001046
|View full text |Cite
|
Sign up to set email alerts
|

Does occupational therapy delay or reduce the proportion of patients that receives thumb carpometacarpal joint surgery? A multicentre randomised controlled trial

Abstract: ObjectivesTo evaluate whether occupational therapy, provided in the period between referral and surgical consultation, might delay or reduce the need of surgery in thumb carpometacarpal joint (CMCJ) osteoarthritis and to explore predictors for CMCJ surgery.MethodsThis multicentre randomised controlled trial included patients referred for surgical consultation due to CMCJ osteoarthritis. An occupational therapy group received hand osteoarthritis education, assistive devices, CMCJ orthoses and exercises. A contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 43 publications
1
38
1
Order By: Relevance
“…Moreover, long-term outcomes after non-operative treatment of painful TMC-OA have not been reported (23). Low quality studies suggest that hand exercise may have a mild positive effect on hand pain, function and finger joint stiffness in the short term (23), however, an occupational therapy regimen has not been shown to significantly delay or reduce the rate of surgery (24). As a growing number of patients, even with few or mild symptoms, are seeking expert opinion on TMC-OA treatment (13,14,25), high-quality research is warranted to aid decision making between non-operative and operative treatment in order to avoid surgical over-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, long-term outcomes after non-operative treatment of painful TMC-OA have not been reported (23). Low quality studies suggest that hand exercise may have a mild positive effect on hand pain, function and finger joint stiffness in the short term (23), however, an occupational therapy regimen has not been shown to significantly delay or reduce the rate of surgery (24). As a growing number of patients, even with few or mild symptoms, are seeking expert opinion on TMC-OA treatment (13,14,25), high-quality research is warranted to aid decision making between non-operative and operative treatment in order to avoid surgical over-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason is that the value of non-operative treatments for TMC osteoarthritis remains unclear and, at present, there is no widely agreed or standardized protocol for non-operative treatment. Gravas et al. (2019) reported that an occupational therapy regime did not significantly delay or reduce the rate of surgery.…”
Section: When Should Patients Be Offered Surgical Treatment?mentioning
confidence: 99%
“…However, this may not always be the case. One study reported that 68% of patients referred for consideration of surgery did not undergo surgery during the following 2 years (Gravas et al., 2019), and I am unaware of any studies that have reported the long-term outcome of painful TMC osteoarthritis that is not treated surgically. In my experience, I have found it sensible to delay surgery for at least 3–6 months after the onset of intolerable pain, or even longer.…”
Section: When Should Patients Be Offered Surgical Treatment?mentioning
confidence: 99%
“…O’Brien et al concluded that receiving non-operative treatment by an OT was the only significant predictor for not requiring surgery among 224 patients referred to a hand surgeon for common hand conditions, such as hand OA [ 23 ]. In a recent randomized controlled trial (RCT), occupational therapy in the waiting period to surgical consultation led to improved function after three months [ 24 ] and less surgery after two years in patients with CMC1 OA [ 25 ]. Furthermore, in an ethnographic study exploring the practice in OT-led hand clinics, the authors conclude that the therapists’ occupational perspective on assessing and addressing activity and participation is as an important and added bonus [ 26 ].…”
Section: Introductionmentioning
confidence: 99%